Immunostimulatory Activity of Lactococcus lactis subsp. lactis CAB701 Isolated from Jeju Cabbage - Huijin Jeong; Suin Kim; Un-Sik Hwang; Hyukjoon Choi; Young-Seo Park (Microorganisms, 2023)
This study explored the potential of Lactococcus lactis subsp. lactis CAB701 as a probiotic strain, focusing on its immunostimulatory properties. Despite adverse conditions in the gastrointestinal environment, this strain exhibited remarkable survivability, as evidenced by its tolerance to acid, bile, and pancreatin, coupled with its impressive ability to adhere to Caco-2 cells. It also exhibited significant antioxidant activity, similar to the established probiotic Lacticaseibacillus rhamnosus GG (LGG). Our research elucidates the potent immunostimulatory effects of L. lactis subsp. lactis CAB701. This strain significantly enhanced nitric oxide production in RAW 264.7, far exceeding that obtained with LGG. An in-depth examination revealed elevated expression of key inflammatory mediators, including inducible nitric oxide synthase, tumor necrosis factor-alpha, cyclooxygenase-2, interleukin (IL)-1 beta, and IL-6. L. lactis subsp. lactis CAB701 increases the expression of critical signaling proteins in the mitogen-activated protein kinase pathway. This prompted a substantial increase in the expression of phosphorylated c-Jun N-terminal kinases and extracellular signal-regulated kinases, suggesting their role in modulating these immune-related pathways. Overall, these findings demonstrate the significant immunostimulatory capacity of L. lactis subsp. lactis CAB701, positioning it as a potential candidate for probiotic use, especially in applications that enhance immune responses.